Is culture measurable? An analysis of the effectiveness of public cultural institutions from the perspective of cultural learning - Pető Lilla (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. In this research, our aim is to examine public cultural institutions and community spaces from the viewpoint of cultural learning. Cultural learning is a form of knowledge acquisition realized through an extensive institutional and instrumental system of culture, categorized under non-formal and informal learning. This type of learning manifests itself with varying intensity and forms and is present throughout all stages of people’s lives [3]. This process aids in building social relationships and understanding and respecting cultural diversity [2]. Within educational sciences, cultural learning within public culture is associated with the subsystem of cultural education, defining and organizing its conceptual framework [4]. The research aimed to investigate whether significant differences exist between various types of public cultural service providers and how effectively they achieve their intended goals. The principle of effectiveness focuses on realizing predefined objectives and achieving planned results [1]. Although this concept can be interpreted in multiple contexts, the central question always remains how successfully an activity or process achieves its goals. Our analysis examined key statistical data from cultural statistics in a time series overview between 2014 and 2023.
Keywords: cultural learning; cultural institution